Assessment of optimal thresholds for ventricular scar substrate characterization using the high density grid multipolar mapping catheter. (19th May 2022) - Bangash, F; Collinson, J; Dungu, J; Gedela, S; Westwood, M; Manisty, C; Farwell, D; Tan, S; Savage, H; Vlachos, K; Silberbauer, J; Calvo, J; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Voltage thresholds for ventricular scar definition are based on historic data collected using catheters with widely spaced bipoles in the absence of contact force. Modern multipolar mapping catheters employ smaller electrodes and interelectrode spacing that theoretically allows for mapping with increased resolution and reduced far-field electrogram (EGM) component. Despite the advancement in technology, historic cut-offs of <0.5mV for dense scar and 0.5-1.5mV for scar borderzone continue to be used in contemporary electrophysiology. Purpose: We aimed to assess the optimal voltage cut-offs for ventricular scar substrate characterization using the HD Grid multipolar mapping catheter. Voltage cut-offs were assessed against cardiac MRI derived scar. We compared optimal voltage cut-offs using conventional bipolar sampling, the Best Duplicate Algorithm and with the HD wave solution plus best duplicate algorithm on. Methods: A multicentre study of twenty patients undergoing VT ablation was conducted. Substrate mapping was performed using the high-density HD-grid multipolar mapping catheter. Bipolar voltage maps were co-registered with cardiac MRI obtained prior to the procedure to assess the voltage characteristics of scar defined by cardiac MRI (CMR) (Figure 1). Pre-procedure contrast enhanced CMR data were analysed using ADAS software (Galgo medical). Data points were collected in regions of scar during (1) HD wave mapping with best duplicate algorithm on(Waveon), (2) Mapping with HD wave off and best duplicate on (Waveoff) and (3) with conventional bipolar mapping (Alloff). Results: The median bipolar voltage for regions of dense CMR scar using (Waveon) HD wave solution and best duplicate algorithm was 0.27mV (IQR 0.14 – 0.46). The median voltage with (Waveoff) HD wave off was 0.29mV (0.15 – 0.45). The median voltage with (Alloff) HD wave off and best duplicate off was 0.32mV (0.19 – 0.5). ROC analysis using AUC suggested the optimal cut-off for endocardial dense scar using (Waveon) HD wave mapping and best duplicate algorithm was 0.30mV (sensitivity: 69.6%, specificity: 60.74%), (Waveoff) cut-off with the best duplicate and without the HD wave mapping was 0.34mV (sensitivity: 69.78%, specificity: 64.46%) and (Alloff) without wave mapping or best duplication was 0.36mV (sensitivity: 84%, specificity: 52%) Figure 2. Conclusion: Ventricular substrate characterization with newer mapping technology using narrow electrode spacing and smaller electrode size suggests that traditional voltage cut-offs may need revision for delineation of scar characteristics. Additionally, the ability to repeat sample in a region to obtain the best signal (Best Duplicate), and the ability to obviate the effect of wavefront direction using the HD wave solution omnipolar technology, may further increase the fidelity of scar characterization. This has important implications for mapping VT and characterizing channels in order to identify VT circuits.